1997
DOI: 10.1111/j.1532-5415.1997.tb03774.x
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Patient Care Staff in Estimating and Documenting Meal Intake of Nursing Home Residents

Abstract: Study findings indicate that the present system used to document nursing home residents' intake is inadequate and that a more accurate mechanism or an entirely different process for identifying residents at risk for nutritional problems should be developed and implemented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
0
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 16 publications
3
39
0
2
Order By: Relevance
“…The results to this question about how much the residents ate from the offered meals in average can only approximately describe the amount of food the residents ate. However, it is known from previous studies that nurses often overestimate the actual food intake significantly among nursing home residents (Pokrywka et al, 1997;Simmons & Reuben, 2000;Suominen et al, 2004). Thus, our findings that nearly half of those suffering from malnutrition ate only half or less from the offered food portion is probably rather an underestimate than overestimate of the true situation.…”
Section: Discussionmentioning
confidence: 97%
“…The results to this question about how much the residents ate from the offered meals in average can only approximately describe the amount of food the residents ate. However, it is known from previous studies that nurses often overestimate the actual food intake significantly among nursing home residents (Pokrywka et al, 1997;Simmons & Reuben, 2000;Suominen et al, 2004). Thus, our findings that nearly half of those suffering from malnutrition ate only half or less from the offered food portion is probably rather an underestimate than overestimate of the true situation.…”
Section: Discussionmentioning
confidence: 97%
“…It is not surprising that a relationship between staffing levels and nutritional status is also observed in the residential care setting. Apart from staff numbers, suitable training is also important, as it had been documented that approximately one-third of nutritionally at risk subjects was not identified by home staff, who also tended to overestimate meal intake by up to 20% (Pokrywka et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported inaccuracies of such charts, especially in residential homes (1,9,10). In one study, onethird of residents whose fluid intake placed them at risk of dehydration were not identified (1).…”
Section: Introductionmentioning
confidence: 99%